Analysis of social change reconsidered - Ponsioen, J. A. (Hague, 1962)
In this book, Professor Ponsioen has sought to consider critically a broad selection of both the first two types of writings on social change and to suggest in a stimulating way how their and his ideas can be brought into the beginnings of a synthesis. His proposed synthesis is a searching and not a finished or dogmatic one. It is a suggestive one on which more work is needed and to which specific research projects can contribute. He quite evidently tries to avoid attachment to any of the warring sects in sociology. The sincerity of his efforts to derive useful contributions from each theorist is refreshing. In consequence of such a constructive approach, his book is full of probing questions and suggested topics for the further development of this significant aspect of social science. Professor Ponsioen's attitude toward terms and conceptions is typical of his inquiring and stimulating treatment. He recognizes that a science with a static terminology is dead. He contends that a good sociologist should be prepared to use various sets of terms and conceptions as intellectual tools; the choice among them depends upon their utility in meeting the needs of the specific problem at hand. t 0ocial change is capricious.
Keywords: Sociology